2014
DOI: 10.1002/etc.2517
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent relative potency factors for polycyclic aromatic hydrocarbons and their derivatives in the H4IIE‐luc bioassay

Abstract: The H4IIE-luc transactivation bioassay for aryl hydrocarbon receptor (AhR) agonists was used to investigate the relative potency factors (REPs) of 22 individual polycyclic aromatic hydrocarbons (PAHs) and their oxygenated-, methylated-, and N-containing derivatives (azaarenes), which are often present in PAH-contaminated soils. Naphthacene and dibenz[ah]acridine exhibited greater AhR-mediated potency, whereas lesser molecular-weight azaarenes were less potent AhR agonists. Six oxygenated PAHs had calculable RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 33 publications
5
20
0
Order By: Relevance
“…The decline in REPs or luciferase activity with increased exposure duration is assumed to be a consequence of metabolic degradation of the PAHs in the cells, resulting from the induction of CYP1A1. This assumption is supported by the findings of previous studies (Jones et al ; Larsson et al ). However, declining REPs can also result from differences in cell density in the wells, potential changes in cell activity because of crowding, or a loss of PACs due to evaporation or adsorption to the plastic wells.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The decline in REPs or luciferase activity with increased exposure duration is assumed to be a consequence of metabolic degradation of the PAHs in the cells, resulting from the induction of CYP1A1. This assumption is supported by the findings of previous studies (Jones et al ; Larsson et al ). However, declining REPs can also result from differences in cell density in the wells, potential changes in cell activity because of crowding, or a loss of PACs due to evaporation or adsorption to the plastic wells.…”
Section: Discussionsupporting
confidence: 89%
“…However, the other O ‐heterocyclic compound tested in the present study (benzo[ b ]naphtho[2,1‐ d ]furan) was more than 10 4 times less potent than was dinaphtho[1,2‐ b ;1′,2′‐ d ]furan at all exposure durations. Comparison of benzo[ b ]naphtho[2,1‐ d ]furan with the parent compound benzo[ a ]fluorene (Larsson et al ) showed that benzo[ b ]naphtho[2,1‐ d ]furan was significantly less potent than its parent PAH and the oxygenated PAH benzo[ a ]fluorenone (Larsson et al ) after 24 h of exposure ( p < 0.5, Student's t test). Dibenzothiophene and its methylated derivatives were also weak AhR inducers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative potencies of ligands to activate the AhR are directly proportional to the affinity with which they bind to the AhR (Kramer and Giesy, 1999). The greater the proportion of occupancy on the receptor, the greater probability of the transformed receptor-ligand complex interacting with the dioxin response enhancer (DRE) on DNA (Farmahin et al, 2013;Lee et al, 2013;Larsson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%